2006
DOI: 10.1039/b511958h
|View full text |Cite
|
Sign up to set email alerts
|

A three-channel microfluidic device for generating static linear gradients and its application to the quantitative analysis of bacterial chemotaxis

Abstract: We have developed a prototype three-channel microfluidic chip that is capable of generating a linear concentration gradient within a microfluidic channel and is useful in the study of bacterial chemotaxis. The linear chemical gradient is established by diffusing a chemical through a porous membrane located in the side wall of the channel and can be established without through-flow in the channel where cells reside. As a result, movement of the cells in the center channel is caused solely by the cells chemotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
234
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(238 citation statements)
references
References 42 publications
3
234
0
1
Order By: Relevance
“…3.3(d) These findings show that the magnitude of the chemoeffector gradient within the test channel will be less than GE (by up to 50%) and the geometry of the system must be accounted for in determining the actual gradient magnitude. This was not recognized in previous studies that reported Qo = 1 based on wide-field fluorescence microscopy measurements [93,94]. The latter, however, is inappropriate for accurate characterization of the test-channel gradients because the out-of-plane fluorescence from the agarose layer, which is considerably thicker than the test channel, can override that of the test channel.…”
Section: Z T-xmentioning
confidence: 57%
See 1 more Smart Citation
“…3.3(d) These findings show that the magnitude of the chemoeffector gradient within the test channel will be less than GE (by up to 50%) and the geometry of the system must be accounted for in determining the actual gradient magnitude. This was not recognized in previous studies that reported Qo = 1 based on wide-field fluorescence microscopy measurements [93,94]. The latter, however, is inappropriate for accurate characterization of the test-channel gradients because the out-of-plane fluorescence from the agarose layer, which is considerably thicker than the test channel, can override that of the test channel.…”
Section: Z T-xmentioning
confidence: 57%
“…4.8. The CMC is a dimensionless metric of the strength of chemotaxis, measured as the degree of non-uniformity in the cell distribution along a spatial gradient, and is defined as [94]:…”
Section: Fcd In Steady Linear Gradientsmentioning
confidence: 99%
“…It is involved in a number of important processes including immune responses, tissue repair, and tumor cell metastasis, and understanding the molecular mechanisms governing directed cell migration is important for the development of new therapeutic strategies. Even though most, if not all, physiological and pathophysiological chemotaxis occurs within 3D environments, most in vitro chemotaxis experiments have been conducted in 2D settings (Abhyankar et al 2006;Boyden 1962;Frevert et al 2006;Irimia et al 2006;Irimia et al 2007;Jiang et al 2005;Li Jeon et al 2002;Shamloo et al 2008;Diao et al 2006;Cheng et al 2007;Sun et al 2008;Zigmond 1977).…”
Section: Introductionmentioning
confidence: 99%
“…These microfluidic channel devices have been fabricated for a linear chemical gradient using various materials, such as agarose, nitrocellulose, PEG, and other variations. 39,[42][43][44] We customized this channel for our purposes and used it to evaluate the chemotaxis of the bacteriobots. In contrast to other studies about bacteriobot motility, we separately considered the effects of environmental bacteria and attached bacteria.…”
Section: Discussionmentioning
confidence: 99%